Integrated Educational Practices for Building Character and Motivation among Orphans in Institutional Care at Ummu Aiman Makassar Islamic orphanage - Luthfiah Nurhuda Watri; Rosmiati; Subaedah; Nurlaelah (Tamaddun Life, 2025)
This study explores the integrated strategies employed by caregivers at Panti Asuhan Ummu Aiman, an Islamic orphanage in Makassar, Indonesia, to strengthen character education and enhance learning motivation among children in institutional care. Using a qualitative phenomenological approach, data were collected through semi-structured interviews with 12 children and 6 caregivers, participant observation over a three-month period, and document analysis. The findings reveal nine interrelated strategies: psychological consultation, tahfidz (Qur’an memorization) programs, caregiver role modelling, structured character education routines, regular monitoring and evaluation, participation in Jakarta Intensive Learning Centre (JILC) tutoring, a balanced reward and punishment system, engagement with external stakeholders, and entrepreneurship training. These strategies function synergistically to address the emotional, moral, cognitive, and social dimensions of the children's development. The study concludes that a holistic and culturally grounded model integrating spiritual, psychological, and educational support can effectively foster character formation and academic motivation in orphanage settings. The implications suggest that faith-based care institutions can play a transformative role when guided by intentional, structured, and empathetic approaches to child development.